Simultaneous Time‐Resolved SAXS and WAXS Study on Guest Exchange Process of Syndiotactic Polystyrene with Aromatic Compounds: Size and Shape Effects of Target Molecules. Issue 1 (January 2016) - Kaneko, Fumitoshi; Seto, Naoki; Sato, Shuma; Sakurai, Shinichi
Summary: One of the important characteristics of syndiotactic polystyrene (sPS) is that it forms cocrystals with a variety of chemical compounds. The guest exchange procedure is an effective method to introduce diverse chemical compounds into the crystalline region of sPS cocrystals; it enables sPS to form cocrystals even with chemical compounds that are difficult to incorporate into the crystalline region by usual crystallization. The original guest in the sPS cocrystal is replaced by another chemical when exposed to a vapor, a liquid or a solution of the new guest. In order to study the characteristics of the guest exchange process initiated by exposure to a liquid, simultaneous time resolved SAXS and WAXS measurements were carried out to follow the structure changes during the guest exchange process. A series of aromatic compounds, benzene, toluene, xylene ( o ‐ and p ‐isomers) and mesitylene were employed as new guests. The simultaneous measurements enabled gathering information concerning both the higher order structure and the cocrystal structure. The exchange from the old guest to the new guest was also followed by FTIR spectroscopy. It is clarified that not only the size of the new guest molecules but also the molecular shape has a significant influence on the guest exchange behavior. It is also suggested that on the liquid‐phase guest exchange an expansion of the lamellar period somewhat precedes the guest exchange in the crystalline lamellae.